2021
DOI: 10.1101/2021.04.02.21254809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for severity on admission and the disease progression during hospitalization in a large cohort of COVID-19 patients in Japan

Abstract: Objectives: To investigate the risk factors contributing to severity on admission. Additionally, risk factors on worst severity and fatality were studied. Moreover, factors were compared based on three points: early severity, worst severity, and fatality. Design: A observational cohort study utilizing data entered in a Japan nationwide COVID-19 inpatient registry, COVIREGI-JP. Setting: As of August 31, 2020, 7,546 cases from 780 facilities have been registered. Participating facilities cover a wide range of h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The present results revealed differences in patient background, clinical findings, disease severity, and clinical outcomes between NHCAP and CAP due to COVID-19. The median age and frequency of comorbid illness, which are associated with greater severity of COVID-19 [ 10 ], were significantly higher in patients with NHCAP than those with CAP ( p < 0.0001). Rates of ICU stay and in-hospital mortality were also significantly higher in patients with NHCAP than those with CAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results revealed differences in patient background, clinical findings, disease severity, and clinical outcomes between NHCAP and CAP due to COVID-19. The median age and frequency of comorbid illness, which are associated with greater severity of COVID-19 [ 10 ], were significantly higher in patients with NHCAP than those with CAP ( p < 0.0001). Rates of ICU stay and in-hospital mortality were also significantly higher in patients with NHCAP than those with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Within Group D, 16 patients were receiving regular endovascular treatment with anti-cancer drugs as an outpatient and 28 patients were receiving dialysis. A large Japanese cohort study demonstrated that patients with solid tumors or receiving dialysis experienced more-severe COVID-19 [ 10 ]. Among patients with NHCAP, the mortality rate was highest at 37.5% in patients with recent cancer treatment, followed by elderly or disabled people who were receiving nursing care with performance status scores of 3 or 4 (Group C, 24.3%), residents of an extended care facility or long-term care health facility (Group A, 23.0%), patients receiving dialysis (13.6%), and patients with mental disorders who were hospitalized in a medical institution for the treatment of mental illness (9.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terada et al conducted a cohort study of 3,376 patients, categorizing them into two groups based on the severity of the infection at the time of admission: 2,199 cases (65.1%) were nonsevere, and 1,181 cases (34.9%) were severe, and observed that obesity had a major effect on the severity of symptoms (OR 1.75; 95% CI 1.26-2.45, p = 0.001) (54).…”
Section: Obesity In Patients With Covid-19 and Disease Severity/compl...mentioning
confidence: 99%